INTEGRASI REMEDIASI MISKONSEPSI TENTANG GELOMBANG MELALUI MODEL PEMBELAJARAN GENERATIF PESERTA DIDIK SMA NEGERI 2 PONTIANAK - Jati Laksono; Haratua Tiur Maria Silitonga; Syukran Mursyid (Universitas Tanjungpura, 2020)
Abstract This study aimed to determine the effectiveness of the integration of misconceptions remediation through generative learning models to reduce misconceptions and increase student learning outcomes about waves in class XI MIPA 2 SMA Negeri 2 Pontianak. The sample in this study was intact group and selected based on the recommendations of the physics teacher. The research instrument consisted of 8 diagnostic test questions and 4 questions of learning outcomes test. (1) There was a significant change in the conceptual of students,(???? 2 count = 131,33 > χ 2 table = 3,84) with df = 1 and α = 5% (2) The decrease in the number of students who misconcepted each concept was 71.6%. (3) The effectiveness of the generative learning model in reducing the number of students who had misconceptions with the value of The Decreasing of Quantity of the student that Misconception (DQM) was 71.6 % classified as high. (4) The effectiveness of the generative learning model in improving student learning outcomes with an N-Gain value of 0.702 was high. Based on the analyzed data it can be concluded that Generative learning model was effective in reducing misconceptions and increasing student learning outcomes. Keywords: Generative Learning Model, Remediation Integration Misconception, Wave